Interaction between immuno-stem dual lineages in jaw bone formation and injury repair - Liu, Ziyi; Luo, Xutao; Xu, Ruoshi (Frontiers in Cell and Developmental Biology, 2024)
The jawbone, a unique structure in the human body, undergoes faster remodeling than other bones due to the presence of stem cells and its distinct immune microenvironment. Long-term exposure of jawbones to an oral environment rich in microbes results in a complex immune balance, as shown by the higher proportion of activated macrophage in the jaw. Stem cells derived from the jawbone have a higher propensity to differentiate into osteoblasts than those derived from other bones. The unique immune microenvironment of the jaw also promotes osteogenic differentiation of jaw stem cells. Here, we summarize the various types of stem cells and immune cells involved in jawbone reconstruction. We describe the mechanism relationship between immune cells and stem cells, including through the production of inflammatory bodies, secretion of cytokines, activation of signaling pathways, etc. In addition, we also comb out cellular interaction of immune cells and stem cells within the jaw under jaw development, homeostasis maintenance and pathological conditions. This review aims to eclucidate the uniqueness of jawbone in the context of stem cell within immune microenvironment, hopefully advancing clinical regeneration of the jawbone.